Conceptualizing Eating Disorder Psychopathology Using an Anxiety Disorders Framework: Evidence and Implications for Exposure-Based Clinical Research - Schaumberg, Katherine (Clin Psychol Rev, 2020)
Eating disorders (EDs) and anxiety disorders (ADs) evidence shared risk and significant comorbidity. Recent advances in understanding of anxiety-based disorders may have direct application to research and treatment efforts for EDs. The current review presents an up-to-date, behavioral conceptualization of the overlap between anxiety-based disorders and EDs. We identify ways in which anxiety presents in EDs, consider differences between EDs and ADs relevant to treatment adaptions, discuss how exposure-based strategies may be adapted for use in ED treatment, and outline directions for future mechanistic, translational, and clinical ED research from this perspective. Important research directions include: simultaneous examination of the extent to which EDs are characterized by aberrant avoidance-, reward-, and/or habit-based neurobiological and behavioral processes; improvement in understanding of how nutritional status interacts with neurobiological characteristics of EDs; incorporation of a growing knowledge of biobehavioral signatures in ED treatment planning; development of more comprehensive exposure-based treatment approaches for EDs; testing whether certain exposure interventions for AD are appropriate for EDs; and improvement in clinician self-efficacy and ability to use exposure therapy for EDs.